Pengembangan Tari Kuda Kepang di Nagari Kurnia Selatan Kecamatan Sungai Rumbai Kabupaten Dharmasraya - Nickse Dwi Setya Primadona; Afifah Asriati (FBS Universitas Negeri Padang, 2023)
This study aims to reveal and describe the Development of Braid Horse Dance in Nagari Kurnia Selatan, Sungai Rumbai District, Dharmasraya Regency. This type of research is qualitative research with descriptive methods. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations and documentation. The steps to analyze the data are to collect the data, describe the data and infer the data. The results showed that the development of the Braid Horse Dance in South Nagari Kurnia can be seen from the movement, floor pattern, accompaniment music, makeup and clothing, the time and place of the performance. The Braid Horse Dance at Sanggar Ngesti Laras Tirto Kencono has been passed down for generations to 4 generations. The development of Kuda Kepang dance in Nagari Kurnia Selatan which was originally only performed at Wetonan events or selamatan events that occurred from 9 or 10 times a year but can now be performed at various events such as weddings, circumcisions, nagari events and Dharmasraya Regency birthday events.